Penyelesaian Sengketa Pengadaan Tanah Untuk Pembangunan Pelabuhan Proyek Strategis Nasional - Dora Alida Kalajukin; Adonia Ivone Laturette; Pieter Radjawane (PATTIMURA Law Study Review, 2026)
A legal action carried out by the government to obtain land for development purposes by providing compensation to those who have rights to the land. who have rights to the land, as stipulated in Law Number 2 of 2012 on Land Acquisition for Development for the Public Interest. In terms of settlement Disputes over land for the public interest as well as in connection with the construction of national strategic project infrastructure, one of which is related to compensation to the ownership of the right to the object (land). which relates to compensation for ownership of rights to the object (land)for such development sometimes causes problems so that the compensation process causes problems between parties who claim to be the owner of the land (object or land). owner of the land (object or land). The research method used in writing this thesis is normative juridical research method. Based on the discussion in this paper by the author, the land acquisition procedure is always guided by existing laws and regulations, then in relation to the settlement of land acquisition disputes for the benefit of the construction of oil refinery port infrastructure which is a national strategic project in the Tanimbar Islands Regency, the settlement can be carried out in 2 ways, namely through non-litigation and litigation channels, thus, the land acquisition procedure is always based on the applicable laws and regulations and in resolving disputes over the issues studied, the procedure is in accordance with the Legislation. Furthermore, in relation to the settlement of land acquisition disputes for the benefit of the development of oil refinery port infrastructure which is a national strategic project in the Tanimbar Islands Regency, the settlement can be carried out in 2 ways, namely through non-litigation and litigation channels, thus, the land acquisition procedure in question is always based on applicable laws and regulations and in resolving disputes over the issues studied, the procedure is in accordance with the Legislation. Furthermore, in the case of the settlement of compensation for land acquisition based on the existing position case, if it has not yet obtained a court decision with permanent legal force, it can be pursued through non-litigation channels either in a family manner with the assistance of the Village Government and the local District Government facilitated by the Provincial Government so that the process of compensation for land and plants on it can be carried out properly and fairly,